CRIMINAL RESPONSIBILITY FOR INCHOATE OFFENCEACCORDING CRIMINAL CODE OF THE REPUBLIC OF UZBEKISTAN - X.Ochilov, D.Kamalova (International Journal of Advanced Science and Technology, 2020)
This article is dedicated to the institute of criminal attempt. The criminal attempt is one of the complicated and important institutes of Criminal law. The correct sentencing for the acts crime interrupted before the commission thereof due to circumstances not depending of a committer person is an expression of priority Principle of Criminal law – principle of Lawfulness. Therefore, researching of legal nature of criminal attempt, analyzing its objective and subjective signs has a very special significance. The author reveals the social danger of criminal attempt, necessity of appointing the criminal responsibility for it. Such types of criminal attempt like completed, uncompleted, fit and unfit criminal attempt are analyzed. On the base of Criminal Code of the Republic of Uzbekistan, recites the problems of sentencing for the criminal attempt as well as given the recommendations for improving and further liberating of criminal legislation.